2020
DOI: 10.1002/ente.202000116
|View full text |Cite
|
Sign up to set email alerts
|

Disentanglement of Degradation Mechanisms by Analyzing Aging Dynamics of Environmentally Friendly Processed Polymer Solar Cells

Abstract: Lifecycle assessments suggest preventing halogenated solvents or solvent additives for environmentally friendly polymer solar cells. Thus, the active layers of polymer:fullerene bulk heterojunction solar cells based on poly{[4,8‐bis‐(2‐ethyl‐hexyl‐thiophene‐5‐yl)‐benzo[1,2‐b:4,5‐b0]dithiophene‐2,6‐diyl]‐alt‐[2‐(20‐ethyl‐hexanoyl)‐thieno[3,4‐b]thiophen‐4,6‐diyl]} (PBDTTT‐CT) and the fullerene derivative [6,6]‐phenyl‐C70‐butyric acid methyl ester (PC70BM) are cast from m‐xylene solutions. Ortho‐vanilline is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…These degradation mechanisms can be accelerated in the presence of light. It has been widely reported that oxidation of interlayers and electrodes leads to the formation of extraction barriers for photogenerated charge carriers 12 . Depending on the energetic landscape of the material system, a photoinduced radicalization of molecular oxygen can lead to rapid degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These degradation mechanisms can be accelerated in the presence of light. It has been widely reported that oxidation of interlayers and electrodes leads to the formation of extraction barriers for photogenerated charge carriers 12 . Depending on the energetic landscape of the material system, a photoinduced radicalization of molecular oxygen can lead to rapid degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Dimerization also occurs in NFAs if the energetic alignment between donor and acceptor allows for back-hole transfer, back-electron transfer, or inter-system crossing 8 , 17 . However, the dominant degradation processes in NFAs include intermixing and demixing of the heterojunction components, which can be controlled to some extent by tuning crystallinity, miscibility, and the diffusion coefficient of the NFA 12 , 16 , 18 , 19 . Structural decomposition of acceptors such as IT-4F 14 , 20 occurs near to zinc oxide surfaces and under the influence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is based on TiO x as the inorganic portion, which has already been effectively employed in both OPVs and perovskite solar cells and have a lower price. We combine that with the popular organic material PDINO, which usually exhibit good film-forming properties, and both, PBDTTT-C-T:PC 71 BM [15] and PM6:Y6 systems were selected for this study. The blending strategy helps reducing the number of processing steps and thus production costs as well as energy consumption, while solving the problem of perforation caused by inorganic materials and form high-quality and uniform thin films, obtain better ohmic contact with the aluminum electrode.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that oxidation of interlayers and electrodes leads to the formation of extraction barriers for photogenerated charge carriers. 12 Depending on the energetic landscape of the material system, photoinduced radicalization of molecular oxygen can lead to rapid degradation. Radicalized oxygen is highly reactive and has the potential to chemically react with most materials used within the device.…”
Section: Introductionmentioning
confidence: 99%
“…8,17 However, the dominant degradation processes in NFAs include intermixing and demixing of the heterojunction components, which can be controlled to some extent by tuning crystallinity, miscibility, and the diffusion coefficient of the NFA. 12,16,18,19 Structural decomposition of acceptors such as IT-4F 14,20 occurs near to zinc oxide surfaces and under the influence of oxygen. In some cases, the device stability can be improved by increasing the molecular planarity.…”
Section: Introductionmentioning
confidence: 99%